2022
DOI: 10.3390/ijerph19159697
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Zero-Waste Behaviours of College Students

Abstract: This study evaluated the recognition and attitude toward microplastic and zero waste among college students and investigated the factors influencing their zero-waste behaviours. The study was conducted from 20 August 2021 to 10 September 2021, including students at a university in G metropolitan city, Republic of Korea. A total of 196 data were analysed. Statements were developed to verify how the use of disposables and the recognition, attitude, and behaviours related to zero waste were affected during the CO… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
1
2
0
1
Order By: Relevance
“…The skewness statistic ranging between -1.343 to -0.076, and with all similar standard deviation errors. Kurtosis statistic shows the value ranging between 5.312 to -0.024, and with similar standard deviation errors [48]. In these results, the skewness statistics are all negatives indicating the finding are consistent with skewed distribution.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…The skewness statistic ranging between -1.343 to -0.076, and with all similar standard deviation errors. Kurtosis statistic shows the value ranging between 5.312 to -0.024, and with similar standard deviation errors [48]. In these results, the skewness statistics are all negatives indicating the finding are consistent with skewed distribution.…”
Section: Resultssupporting
confidence: 68%
“…It is interesting to note that in this table, both actual and predicted Cronbach values are within the acceptable range, and in fact, the actual data shows an excellent acceptability than predicted Cronbach values, with a minimum value of 0.87, which shows the consistency of the questions being set. Several researchers with similar methods of data collection have tested their questionnaires through pilot studies, but unfortunately, most could not fully determine the consistencies of the questions because they could not achieve the desired Cronbach value [48]. A phenomenon known as multicollinearity may be present when the independent variables are significantly related with one another and with one another with one another.…”
Section: Resultsmentioning
confidence: 99%
“…Sustainable thinking generates valuable information for marketing entities that will influence consumers when making purchasing decisions. In a study by Choi et al (2022) investigated the recognition and attitude toward MPs and zero waste, it was shown that the recognition of the adverse effect of MPs on health was a significant factor in promoting zero waste awareness and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Konsep zero waste memiliki 3 prinsip Reduce, Reuse dan Recycling yang mana prinsip tersebut sebagai landasan membentuk kesadaran perilaku terhadap sampah (S. Lestari et al, 2021). Pada penelitian Choi et al (2022) faktor-faktor yang mempengaruhi zero waste di perguruan tinggi adalah (1) mendorong perilaku tanpa limbah, mahasiswa perlu disosialisasikan terkait pentingnya dampak kesehatan mikroplastik dan sikap pemisahaan sampah; (2) untuk dapat meningkatkan kesadaran dan sikap mahasiswa ada kerjasama dengan perguruan tinggi atau seperti membangun sistem yang menyediakan pendidikan tanpa limbah; dan (3) strategi kampanye disesuaikan dengan semua kelompok umur, sehingga dapat berkontribusi pada penyebaran perilaku zero waste. Dengan adanya penelitian tersebut, bisa diterapkan di sekolah sebagai langkah konkrit menuju sekolah tanpa sampah.…”
Section: A Latar Belakangunclassified